Mitigating flood losses using disaster risk reduction (DDR) model: a case of Kelantan - Tengku Faris Fakhri Tengku Adnan
Flood is a major natural disaster in Malaysia. Yearly, an estimated of 29,800 square kilometres are flooded, affecting 4.82 million people, and causing physical damages amounting up to RM915 million. Recently, Malaysia has been hit by flood disaster through massive flooding in the East Coast States of Peninsular Malaysia in December 2014 that caused huge financial losses amounting to RM1.846 billion. Thus, serious attention by government is very much needed at this point in time to mitigate the flood losses. Nowadays, Disaster Risk Reduction (DRR) has become a new approach in mitigating risks related to the natural disasters. Therefore, the objectives of this study are i) to identify the existing DRR framework to mitigate flood losses, ii) to examine the challenges in mitigating flood losses, and iii) to develop a DRR framework to effectively mitigate future flood risk. The research approach of this study was qualitative and semi structured interview method was used to collect data. Seven organisations that were involved in the disaster management in the state of Kelantan were interviewed. Data has been analysed by using Atlas.ti version 7. This study found that Malaysia already has a DRR framework but there was a lack of awareness and understanding among the organisations about the framework. Besides that, many issues and challenges were identified. The main challenges that faced by the organisations are communication problem and lack of asset during the rescue operations. In this study, a comprehensive DRR model was developed for mitigating flood losses. The results of this study provide a significant contribution in reducing government burden associated with flood disaster in the future.